Abstract 212: Percutaneous Carotid access in Mechanical Thrombectomy ‐ a safe alternative to transfemoral approach - Sonia Bellara; James Hiana; Daniel Zumofen; Yohannes Mulatu (Stroke: Vascular and Interventional Neurology)
Introduction Emergent percutaneous carotid artery MER approach for acute ischemic large vessel strokes are rare given the risk of complications and seldom reported. Methods 75‐year‐old left‐handed functional male (mRs:0) with past medical history of HTN, HLD presented to ED after being found on the floor by his family with slurred speech, new onset right sided weakness, with a last known well of 17 hours. NIHSS on arrival was 14 for expressive aphasia, right visual field defect, right facial weakness, significant dysarthria, right hemiparesis, and sensory defect. CT Head demonstrated left MCA territory early ischemic changes. CTA head/neck demonstrated left M1 occlusion with large penumbra. Perfusion data demonstrated no area of core infarct with area of ischemic penumbra in the left MCA territory involving the left frontal, temporal and parietal lobes measuring 161 ml. ASPECT score 5‐6. The patient was deemed a candidate for mechanical endovascular thrombectomy (MER). The procedure was initiated via ultrasound‐guided right common femoral access. After multiple attempts using a wide range of techniques and wire/catheter combinations in order to establish left intracranial access and given extreme angulation/tortuosity/elongation in the proximal left common carotid artery, it was decided to proceed with the catheter position in the left common carotid or the left internal carotid artery that would allow for subsequent catheterization of the intracranial circulation for MER. Results Near complete revascularization with minimal distal thrombus material beyond endovascular reach corresponding to a TICI 2C degree of revascularization was achieved. Closure of the femoral puncture site was performed using an Angio seal femoral closure device. Surgical closure of the puncture site was performed by vascular surgery. The patient was eventually discharged to short term acute rehabilitation and continues to follow up outpatient with the Stroke clinic. Conclusion Older patients with ischemic stroke commonly have tortuous vessels or peripheral vascular disease. As a result, they may greatly benefit from emergent direct carotid access, as the trans‐femoral approach often poses challenges in accessing the thrombus. For patients with complex and unfavorable vascular anatomy for mechanical endo‐vascularization, direct percutaneous carotid puncture can be advantageous, effectively reducing the aforementioned difficulties. When opting for such an approach it is vital to factor in the aortic arch appearance and its branches.